1985
DOI: 10.1111/j.1533-8525.1985.tb00220.x
|View full text |Cite
|
Sign up to set email alerts
|

The Feminist Critique and A Decade of Published Research in Sociology Journals

Abstract: In the mid to early 1970s feminist writers raised four major criticisms about sociological research on women and expressed concern about the related issue of the discipline's treatment of women sociologists. Critics charged that sociological research underrepresented women as subjects, concentrated on research topics more central to men's than to women's lives, used concepts, paradigms, methods, and theories better portraying men's than women's lives, and used men and male experience as norms against which all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
3

Year Published

1990
1990
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 44 publications
0
61
0
3
Order By: Relevance
“…We begin by documenting the number of gender-content articles in fifteen professional journals and assess fluctuations over a ten-year period. The 1984-1993 time period was selected because the only other empirical study of the incorporation of gender-content scholarship into sociology journals covered a ten-year period ending in 1983 (see Ward and Grant 1985).…”
Section: Methods: Operationalization Issues and Data Sourcementioning
confidence: 99%
See 3 more Smart Citations
“…We begin by documenting the number of gender-content articles in fifteen professional journals and assess fluctuations over a ten-year period. The 1984-1993 time period was selected because the only other empirical study of the incorporation of gender-content scholarship into sociology journals covered a ten-year period ending in 1983 (see Ward and Grant 1985).…”
Section: Methods: Operationalization Issues and Data Sourcementioning
confidence: 99%
“…While informal discussions of this issue are frequent in the academy, many are based more on personal observations than on systematic empirical research. Thus, to date, limited empirical research exists which systematically assesses the incorporation of gender-content scholarship into sociology, with the notable exception of Ward and Grant's (1985) and Grant and Ward's (1991) examination of gender and feminist scholarship in sociology journals between 1974 and 1983.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Even the question of whether this diversity has affected sociology's "voice," however, was a matter of debate for a while. Thus, while their evidence covered only about a decade of change after early 1970s feminist writers had critiqued the field, Ward and Grant (1985) reported that women had had "little or only limited impact" (1985: 139) on what was being said in sociology's professional journals. Not only were sociology articles less focused on gender and feminist concerns than Ward and Grant felt they should be by 1983, but the representation of female authors had actually declined from 22 percent of solo authors in 1975 to 21 percent in 1983.…”
Section: Diversity As Problem or Solutionmentioning
confidence: 96%